Next generation access networks: infrastructure sharing - Pereira, João Paulo (2017)
The migration to Next Generation Access Networks (NGAN) has raised a range of issues related to building wiring and infrastructure sharing. The deployment strategies for operators and entrants are completely diﬀerent. European Commission argues that infrastructure-based competition is the best and fastest way for broadband development. The arguments are that infrastructure based competition provides eﬃciency incentives to operators, reduces prices, increase penetration, stimulates innovation, etc. However, civil costs represent up to 80% of the total roll-out cost of NGA. The study deployed shows several broadband access infrastructure sharing solutions.